Contratación igual o inferior a 8 UIT y la calidad de gasto público en la Gerencia Regional de Tecnologías de la Información del Gobierno Regional de Loreto año 2025 - Catashunga Mariño, Lisandro (2025)
The study investigated the relationship between procurement equal to or less than 8 Tax Units (UIT) (V1) and the quality of public spending (V2) in the Regional Management of Information Technologies of the Regional Government of Loreto (GORE Loreto) for the year 2025. A basic, quantitative, descriptive-correlational methodology was employed, with a non experimental, cross-sectional design, administering a questionnaire to a census sample of 20 workers from said management. The general results, despite a mixed perception of V1 (with 40% considering it good and 60% fair or poor) and 50% favorability for V2, revealed a direct, high, and statistically very significant Spearman's Rho of 0.872, and a Sig. = 0.000 between both variables. The general conclusion is that better management in procurement equal to or less than 8 UIT is strongly linked to a higher perceived quality of public spending, thus validating the main research hypothesis. This robust finding underscores the importance of optimizing these contractual processes to positively influence the perception of spending quality.